Anti-hypoglycemic effect of aqueous leaf extract of Siamese neem tree (Azadirachta indica) in Plasmodium berghei infected mice - V. Somsak (2018)
© 2008 IFRJ. Hypoglycemia has been reported during malaria infection in blood stage, and can cause of death in malaria endemic countries. Hence, in this study was aimed to evaluate anti-hypoglycemic effect of Siamese neem tree extract in P. berghei infected mice. The aqueous leaf extract of Siamese neem tree was freshly prepared and used for orally treatment. Groups of ICR mice were infected intraperitoneally with 6x106 infected erythrocytes of P. berghei ANKA, and subsequently given with the extract twice a day for 4 consecutive days. Blood glucose levels were then measured. Normal and untreated mice were used as healthy and disease controls, respectively. The results showed that hypoglycemia was developed during P. berghei ANKA infection in mice as indicated by decreasing of blood glucose level. However, blood glucose level in the extract treated mice was similar to normal group. It can be summarized that aqueous leaf extract of Siamese neem tree exhibited anti-hypoglycemic effect against P. berghei ANKA infected mice.